Assessing Service Quality, Product Quality, And Brand Image On Repurchase Intention Through Customer Satisfaction At Arunika Restaurant Palembang: A Pilot Study - Imanullah, Noorharsy; Indrawati, Indrawati (Publisher Cv. Inara, 2025)
In Palembang’s increasingly competitive food and beverage (F&B) industry, customer retention has become a pressing challenge for businesses like Arunika Restaurant. Despite serving over 1,600 customers monthly, the restaurant faces fluctuating sales and limited product differentiation in a market where digital engagement plays a critical role. This study investigates the influence of service quality, product quality, and brand image on repurchase intention, with customer satisfaction as a mediating variable. A pilot test was conducted with 30 Arunika customers using a structured questionnaire distributed via face-to-face interactions and completed through Google Forms. The data were analyzed using SPSS to assess the instrument’s validity and reliability. All items demonstrated Corrected Item Total Correlation (CITC) values above 0.3 and Cronbach’s Alpha values exceeding 0.7 (Indrawati, 2015). Furthermore, loading factors surpassed 0.70, AVE values exceeded 0.50, and Composite Reliability (CR) values ranged from 0.871 to 0.909, confirming strong internal consistency and convergent validity (Hair et al., 2022). These results support the instrument’s suitability for use in further analysis of repurchase behavior in the F&B sector.